Clinging to a barbed wire fence: the language policy of the international community in Bosnia-Herzegovina since 1995 - Askew, Louise (2011)
This study takes one aspect of the post-conflict peace-building process in Bosnia- Herzegovina since 1995 - the recognition of three official but mutually comprehensible languages - and examines the way in which the international community's approach to it has impacted on broader peacebuilding goals for the country. The originality of this thesis lies in the fact that it views post-conflict peace-building in Bosnia-Herzegovina through the lens of the language issue. Taking the Dayton Peace Agreement (1995) as the starting point I look at the way in which its provisions have largely dictated the international community's approach to the language issue and created the political environment in which language operates. Further, applying the concept of societal security I explain how the language issue is used by domestic elites to frustrate attempts at reconciliation by the international community; I argue that the international community's approach, based on the equality of the three languages, only feeds into the divisive ethnic politics of present-day Bosnia-Herzegovina and ultimately undermines the security and stability of the country. I also look in detail at two very different but complimentary areas of ongoing post- conflict reform in Bosnia-Herzegovina and analyse the international community's approach to language in each: reform of the education system and defence reform. In the former the language issue cannot be divorced from the identity-formation goals of domestic elites in the education reform. The international community's approach to language in this regard has been counterproductive and has only bolstered attempts to maintain segregation in schools. In the area of defence reform the focus of language policy is not on issues of identity but on the translation and interpretation policy of the international military force which is guided by locally-hired interpreters and translators. I use narrative theory (Baker, 2006) to explain how they negotiate issues of identity, loyalty and ethics and argue that through their influence policy has been more flexible and able to adapt to the requirements of the defence reform. Finally I contend that the international community has tended to view language as an unimportant element of its activities in Bosnia-Herzegovina. This study argues that far from this being the case the international community's approach to language holds important lessons for future peacebuilding endeavours elsewhere.